Finite volume method for solving a one-dimensional parabolic inverse problem - Wang, Bo; Zou, Guang-an; Zhao, Peng; Wang, Qiang (Applied mathematics and computation, 2011)
In this paper, finite volume method is used to solve a one-dimensional parabolic inverse problem with source term and Neumann boundary conditions for the first time. Some advantages of this approach are developing difference schemes and maintaining certain properties of the physics of the problems, especially for the treatment of the source term and the unknown boundary conditions. Numerical results show that our method is more effective.